Dual nanomechanics in anisotropic porous covalent organic framework janus-type thin films - Mohata, Shibani; Dey, Kaushik; Bhunia, Surojit; Thomas, Neethu; Gowd, E. Bhoje; Ajithkumar, Thalasseril G.; Reddy, C. Malla; Banerjee, Rahul (Journal of the American Chemical Society, 2022)
Empowered by crystalline ordered structures and homogeneous fabrication techniques, covalent organic frameworks (COFs) have been realized with uniform morphologies and isotropic properties. However, such homogeneity often hinders various surface-dependent properties observed in asymmetric nanostructures. The challenge remains to induce heterogeneity in COFs by creating an asymmetric superstructure such as a Janus thin film. In this regard, we propose a versatile yet straightforward interfacial layer-grafting strategy to fabricate free-standing Janus-type COF-graphene thin films. Herein, two-dimensional graphene sheets were utilized as the suitable grafter due to the possibility of noncovalent interactions between the layers. The versatility of the approach was demonstrated by fabricating two distinct Janus-type films, with the COF surface interwoven with nanofibers and nanospheres. The Janus-type films showcase opposing surface morphologies originating from graphene sheets and COF nanofibers or nanospheres, preserving the porosity (552-600 m(2) g(-1)). The unique surface chemistries of the constituent layers further endow the films with orthogonal mechanical properties, as confirmed by the nanoindentation technique. Interestingly, the graphene sheets favor the Janus-type assembly of COF nanofibers over the nanospheres. This is reflected in the better nanomechanical properties of COFfiber-graphene films (E-gra(phene) = 300-1200 MPa; E-COF( )= 15-60 MPa) compared to the COFsphere-graphene films (E-gra(phe)ne = 11-14 MPa; E-CO(F )= 2-5 MPa). These results indicate a direct relationship between the mechanical properties and homo/heterogeneity of Janus-type COF films.

Fast self-healing in a layered molecular crystal mediated by stress-induced symmetry breaking - Ghosh, Ishita; Biswas, Rabindra; Tanwar, Manushree; Bhunia, Surojit; Das, Kaustav; Torris, Arun; Mondal, Amit; Raghunathan, Varun; Kumar, Rajesh; Reddy, C. Malla (Nature Communications, 2026)
In recent years, symmetry-breaking has emerged as a powerful tool for significantly altering various physical properties in 2D layered materials. However, the breaking of symmetry by means of mechanical stress in organic crystals remains elusive. Here, we demonstrate a simple approach to engineer symmetry-breaking through mechanical stress fields in a layered molecular crystal, resulting in autonomous and fast self-healing under ambient temperature and pressure conditions. Fracture mechanics analysis reveals that the crystal adheres to an elasto-plastic model, with formation of a plastic zone at the crack tip, which prevents further crack propagation, facilitating the self-healing process. Spatially resolved Raman mapping reveals that the crack formation is accompanied by a distinct symmetry-breaking mechanism at the microstructural level. A six-fold increase in non-linear second harmonic (SH) activity, triggered by mechanical perturbation, further validates the local symmetry breaking in an otherwise centrosymmetric crystal. Furthermore, symmetry is restored following successful healing, as evidenced by the disappearance of the SH signal in the healed regions. This study not only broadens the scope of self-healing mechanisms viable in molecular materials but also offers key insights into the role of symmetry breaking and its potential for related technological applications.